Inverse scattering approach for massive Thirring models with integrable type-II defects - Aguirre, Alexis Roa [UNESP] (Iop Publishing Ltd, 2012)
We discuss the integrability of the bosonic and Grassmannian massive Thirring models in the presence of defects through the inverse scattering approach. We present a general method to compute the generating functions of modified conserved quantities for any integrable field equation associated with the m x m spectral linear problem. We apply the method to derive in particular the defect contributions for the number of occupation, energy and momentum of the massive Thirring models.